Health care seeking behaviour during pregnancy, delivery and the postnatal period in Bangladesh: Assessing the compliance with WHO recommendations. (August 2018) - Islam, M. Mazharul; Masud, Mohammad Shahed
Highlights: 30% mothers had four or more antenatal care visits as recommended by WHO. 63% deliveries occurred in a non-health facilities. 36% mothers received no postnatal care visit. 18.5% mothers achieved the WHO recommended optimal level of maternal care. A number of factors appeared as significant predictors of maternal care. Abstract: Background: The World Health Organization (WHO) recommends four antenatal care (ANC) visits, delivery in a health facility and three postnatal care (PNC) visits for women to optimize the maternal health outcomes. Objectives: To examine the level and determinants of maternal health care seeking behaviour during pregnancy, delivery and the postnatal period, and assess the compliance with the WHO recommended levels of care in Bangladesh. Design/setting: The study is based on secondary analysis of the data obtained from the 2014 Bangladesh Demographic and Health Survey (BDHS). The 2014 BDHS was a cross-sectional survey of a nationally representative sample of 17, 863 ever-married women aged 15–49 years. The sample was selected following a two-stage stratified cluster sampling design. Participants: The dataset from a subsample of 4.627 ever-married women who had delivered their last birth within three years before the survey were included in the analysis to meet the objectives of the study. Analysis: Descriptive statistics and multinomial logistic regression model were used for data analysis. Findings: It has been observed that only 31% mothers had recommended four or more ANC visits, 37% births were delivered at health facilities, and 65% mothers received at least one PNC visit. Only 18.0% mothers received the WHO recommended optimal level of four or more ANC visits, births in a health facility and at least one PNC visit. Mothers aged less than 20 years, living in rural area, having no education and media exposure, multiparous, poor wealth status, husband with no education and husband's employment status appeared as significant predictors of optimal level maternal health care after adjusting for other factors. Mothers living in Sylhet, Chittagong and Barisal regions were less likely to receive the optimum level health care. Key conclusion: Utilization of maternal health care during pregnancy, delivery and the postnatal period among Bangladeshi women does not reflect the complete compliance with the WHO recommendations. Further studies are needed to identify the reasons for underutilization of optimum level maternal care practice in Bangladesh. Implication for practice: The findings underscore the need for targeted intervention for those groups of mothers who were identified as having lowest level of maternal care across the continuum of care.